Physiological importance of the coronary arterial blood supply to the rattlesnake heart - Hagensen, Mette K.; Abe, Augusto Shinya; Falk, Erling; Wang, Tobias (Company of Biologists Ltd, 2008)
The reptilian heart consists of a thick inner spongy myocardium that derives its oxygen and nutrient supply directly from the blood within the ventricular cavity, which is surrounded by a thin outer compact layer supplied by coronary arteries. The functional importance of these coronary arteries remains unknown. In the present study we investigate the effects of permanent coronary artery occlusion in the South American rattlesnake (Crotalus durissus) on the ability to maintain heart rate and blood pressure at rest and during short term activity. We used colored silicone rubber (Microfil) to identify the coronary artery distribution and interarterial anastomoses. The coronary circulation was occluded and the snakes were then kept for 4 days at 30 degrees C. Microfil injections verified that virtually all coronary arteries had successfully been occluded, but also made visible an extensive coronary supply to the outer compact layer in untreated snakes. Electrocardiogram (ECG), blood pressure (P(sys)) and heart rate (f(H)) were measured at rest and during enforced activity at day 1 and 4. Four days after occlusion of the coronary circulation, the snakes could still maintain a P(sys) and f(H) of 5.2 +/- 0.2 kPa and 58.2 +/- 2.2 beats min(-1), respectively, during activity and the ECG was not affected. This was not different from sham-operated snakes. Thus, while the outer compact layer of the rattlesnake heart clearly has an extensive coronary supply, rattlesnakes sustain a high blood pressure and heart rate during activity without coronary artery blood supply.
Keywords: reptile; coronary artery occlusion; blood pressure; heart rate; Microfil